Change in altitudinal distribution of Newfoundland Gray-cheeked Thrush (Catharus minimus minimus) revealed through historical stop-level breeding bird survey data - Gabrielle Robineau-Charette; Darroch M. Whitaker; Ian G. Warkentin (Journal of Field Ornithology, 2023)
Breeding bird survey (BBS) data are typically analyzed at the route level in which the average or combined total number of individuals across the 50 stops is treated as a single observation. However, analysis at the stop level may provide information on finer-scale habitat affiliations of species within the broader landscape, as well as changes in species distribution over time. Though once abundant, the Newfoundland Gray-cheeked Thrush (Catharus minimus minimus) underwent a dramatic population collapse across most of the island during the 1980s and 1990s and today is most common in montane forests. The reason for this collapse is not well understood but introduced North American red squirrels (Tamiasciurus hudsonicus), which colonized most forested areas on the island below ~400 m from the late 1970s through the mid-1990s, have been identified as a possible cause. To improve our understanding of changes in the elevational distribution of Gray-cheeked Thrushes, we compared stop-level BBS data from two periods. Our historic period from 1974-1984 corresponds with the initial expansion phase of introduced red squirrels, whereas that from 2000-2015 reflects a period during which the colonization of suitable habitat by squirrels was complete. We used 17 routes (850 stops) where the thrushes had been observed and there were at least 3 surveys completed during each period. Surveys during the 1970s and 1980s indicated that Gray-cheeked Thrushes were abundant at all elevations sampled by the BBS (0-450 m), with higher incidence below 100 m and above 300 m; in contrast, recent surveys indicate that the species is now essentially absent below 350 m. This finding highlights the value of historical stop-level BBS data for reconstructing changes in species distributions and is consistent with the hypothesis that red squirrels have adversely affected Newfoundland Gray-cheeked Thrushes.